Pyrrhotite and associated sulphides and their relationship to acid rock drainage in the Halifax Formation, Meguma Group, Nova Scotia - Fox, Don; Robinson, Clare; Zentilli, Marcos (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1997)
The physical disruption of sulphide-bearing mctasedimentary rocks of the Halifax Formation leads to oxidation of iron-sulphide minerals and the generation of acid rock drainage (ARD). Although pyrrhotite occurs in many places throughout the Halifax Formation, previous ARD studies have not considered in detail the mineral chemistry, texture, and distribution of this mineral nor how these factors may potentially influence the development of ARD. For this study, pyrrhotite-bearing samples of the Halifax Formation were collected in the field and from drill core at four locations in southwestern Nova Scotia. Samples were taken from different geological settings, such as proximal and distal to granitic intrusions and from different stratigraphic positions, to obtain a variety of mineral assemblages. Petrographic, microprobe and X-ray diffraction work indicate that the pyrrhotite in all samples is mainly monoclinic Fe7Sg, and its composition is relatively homogeneous regardless of geological environment. Inclusions of chalcopyrite and detectable quantities of As, Co and Ni are common. In regionally metamorphosed, grecnschist-facies areas, pyrrhotite is preferentially aligned along cleavage planes and thus is easily accessible to oxidizing air and fluids. Because pyrrhotite is regionally developed, contains potentially toxic trace elements, and occurs along cleavage planes, it is considered to play a significant role in ARD development in the Halifax Formation. Also, pyrrhotite oxidizes substantially faster than many other sulphide minerals and may be especially significant in the early stages of ARD.